Diagnosis, Genetics, and Therapy of Short Stature in Children: A Growth Hormone Research Society International Perspective - Collett-Solberg, Paulo F.; Ambler, Geoffrey; Backeljauw, Philippe F.; Bidlingmaier, Martin; Biller, Beverly M.K.; Boguszewski, Margaret C.S.; Cheung, Pik To; Choong, Catherine Seut Yhoke; Cohen, Laurie E.; Cohen, Pinchas; Dauber, Andrew; Deal, Cheri L.; et al. (Hormone research in paediatrics, 2019)
The Growth Hormone Research Society (GRS) convened a Workshop in March 2019 to evaluate the diagnosis and therapy of short stature in children. Forty-six international experts participated at the invitation of GRS including clinicians, basic scientists, and representatives from regulatory agencies and the pharmaceutical industry. Following plenary presentations addressing the current diagnosis and therapy of short stature in children, breakout groups discussed questions produced in advance by the planning committee and reconvened to share the group reports. A writing team assembled one document that was subsequently discussed and revised by participants. Participants from regulatory agencies and pharmaceutical companies were not part of the writing process. Short stature is the most common reason for referral to the pediatric endocrinologist. History, physical examination, and auxology remain the most important methods for understanding the reasons for the short stature. While some long-standing topics of controversy continue to generate debate, including in whom, and how, to perform and interpret growth hormone stimulation tests, new research areas are changing the clinical landscape, such as the genetics of short stature, selection of patients for genetic testing, and interpretation of genetic tests in the clinical setting. What dose of growth hormone to start, how to adjust the dose, and how to identify and manage a suboptimal response are still topics to debate. Additional areas that are expected to transform the growth field include the development of long-acting growth hormone preparations and other new therapeutics and diagnostics that may increase adult height or aid in the diagnosis of growth hormone deficiency.